Tax Policy : Designing and Drafting a Domestic Law to Implement a Tax Treaty - Nakayama, Kiyoshi (Technical Notes and Manuals; Technical Notes and Manuals ;, 2011)
Technical Notes and Manuals are produced by IMF departments to expand the dissemination of their technical assistance advice. These papers present general advice and guidance, drawn in part from unpublished technical assistance reports, to a broader audience. This new series was launched in August 2009.